Staphylococcus aureus - Fouch, Sarah (Henry Stewart Talks, 2024)
Characteristics of Staphylococcus aureus, Staphylococcus aureus generates a wide range of clinical infections, Skin syndrome, Tampons and toxic shock syndrome, Common cause of bacteraemia, Structural components, toxins and enzymes that promote infectivity